The activin signaling transcription factor Smox is an essential regulator of appendage size during regeneration after autotomy in the crayfish. Issue 1 (26th December 2018) - Shinji, Junpei; Gotoh, Hiroki; Miyanishi, Hiroshi; Lavine, Mark D.; Lavine, Laura Corley
Abstract : Members of the phylum Arthropoda, comprising over 80% of total animal species, have evolved regenerative abilities, but little is known about the molecular mechanisms mediating this process. Transforming growth factor β (TGF‐β) signaling mediates a diverse set of essential processes in animals and is a good candidate pathway for regulation of regeneration in arthropods. In this study we investigated the role of activin signaling, a TGF‐β superfamily pathway, in limb regeneration in the crayfish. We identified and cloned a downstream transcription factor in the activin pathway, Smox, and characterized its function with regard to other elements of the activin signaling pathway. Gene knockdown of Smox by RNAi induced regeneration of complete but smaller pereopods after autotomy. This indicates that activin signaling via Smox functions in regulation of pereopod growth and size. The expression levels of both Smox and the activin receptor babo were closely correlated with molting. The expression level of Smox increased when babo was knocked down by RNAi, indicating that Smox and babo transcription are linked. Our study suggests that the Babo‐Smox system in activin signaling is conserved in decapods, and supports an evolutionary conservation of this aspect of molecular signaling during regeneration between protostomes and deuterostomes.